Fetal congenital heart disease - mode of delivery and obstetrical complications - Keren Zloto; Alyssa Hochberg; Kinneret Tenenbaum-Gavish; Alexandra Berezowsky; Shiri Barbash-Hazan; Ron Bardin; Eran Hadar; Anat Shmueli (BMC, 2022)
Abstract Background The optimal mode of delivery in cases of fetal congenital heart disease (CHD) is not established. The few relevant studies did not address operative vaginal delivery. The aim of this study was to assess the impact of fetal CHD on mode of delivery during a trial of labor, and to secondarily describe some obstetric complications. Methods The database of a tertiary medical center was searched for women who gave birth to a singleton, liveborn neonate in 2015-2018. Mode of delivery was compared between women carrying a fetus with known CHD and women with a healthy fetus matched 1:5 for maternal age, parity, body mass index, and gestational age. Results The cohort included 616 women, 105 in the CHD group and 511 in the control group. The rate of operative vaginal delivery was significantly higher in the CHD group (18.09% vs 9.78%, OR 2.03, 95% CI 1.13-3.63, p = 0.01); the difference remained significant after adjustment for nulliparity and gestational age at delivery (aOR 2.58, 95% CI 1.36-4.9, p < 0.01). There was no difference between the CHD and control group in rate of intrapartum cesarean delivery (9.52% vs 10.76%, respectively, OR 0.97, 95% CI 0.47-1.98, p = 0.93). The most common indication for operative vaginal delivery was non-reassuring fetal heart rate (78.94% vs 64%, respectively). Median birth weight percentile was significantly lower in the CHD group (45th vs 53rd percentile, p = 0.04). Conclusions Our findings suggest that operative vaginal delivery, performed mostly because of non-reassuring fetal heart rate, is more common in pregnancies complicated by a prenatal diagnosis of CHD than non-anomalous pregnancies.